Thermomechanical processing environment and morphology development of a thermotropic polymer liquid crystal - Viana, J. C. (2010)
We have studied a longitudinal polymer liquid crystal consisting of poly(ethylene terephthalate) (PET) and p-hydroxybenzoic acid, namely PET/0.6PHB, where 0.6 is the mole fraction of the second component. The material was injection molded with systematic variations of the melt and mold temperatures and injection flow rate using design of experiments based on a Taguchi orthogonal array. Thermomechanical environment defined by local melt temperatures and shear rates and stresses imposed during processing was estimated by computer simulations of the mold-filling phase. The morphology of the moldings was characterized by optical and scanning electronic microscopy, wide- and small-angle X-ray scattering, and differential scanning calorimetry. An analysis of variance approach identified the significant processing variables and their contributions to variations of morphological parameters. The processing environment affects strongly the melt viscosity, and there is a strong thermomechanical coupling. The result is a complex multilaminated and hierarchical microstructure, whose morphological features are very sensitive to the processing conditions. Relationships between local thermomechanical variables (rather than global ones) and the morphological parameters are established.